Diversity of Bacteria and Yeasts on the Surface of Table Grapes - Attila Kántor; Miroslava Kačániová (Scientific Papers Animal Science and Biotechnologies, 2023)
Grapes are natural habitat for many different groups of microorganisms. The main groups of microorganisms that colonize the surface of the grapes are: yeasts, acetic acid bacteria and lactic acid bacteria. Grape berry surface is an unstable habitat that changes greatly according to the stage of grape ripening. The aim of this study was to isolate and identified wide range of different groups of microorganisms which colonize the grape berries. We used table grape cultivars Red Globe (red) and Sundance (white) in this study. Table grapes are grapes intended for consumption and different than grapes which use in winemaking. Bacterial and yeast species identified by MALDI-TOF MS Biotyper. We determine 12 yeasts and 30 species of bacteria. The dominant genera of microorganisms were Bacillus, Candida, Lactobacillus, Staphylococcus and Aureobasidium.  We also identified 4 different strains of Saccharomyces cerevisiae.